Aetiological and Clinical Pattern of Severe Anaemia in a Tertiary Care Hospital at Rajshahi, Bangladesh - Hoque, Md Azizul; Akhter, Khaleda; Islam, Md Daharul; Ali, Syed Mohammad Monowar; Rahman, Md Zillur; Haque, Md Shariful; Azhar, MA (KYAMC Journal, 2017)
Background: Anaemia is a common health problem encountered in our day to day medical practice. It occurs in every age groups, in both sexes in every communities and all countries. Objective: To find out the aetiological pattern and clinical profile of severe anaemia for prompt diagnosis an droper management. Materials and Methods: The prospective study was carried out in different Medicine unit at Rajshahi Medical College Hospital (RMCH), Rajshahi on consecutive 100 hospital admitted patients having severe anaemia. All underwent routine and some special investigations for severe anaemia. Results: Peak age incidence was 20-29 years (38%) and sex incidence was male (68%). Most of the patients were farmers (38%). Common monthly income group was >2000-5000 (48%). Incidence of severe anaemia was aplastic (26%), leukaemia (24%), haemolytic (22%), anaemia of chronic disorder (10%), iron deficiency anaemia (9%) and anaemia of chronic renal failure (9%). Peak age incidence for aplastic anaemia was 20- 29 years (42.3%), for leukaemia 14-19 years 33.3%), for haemolytic anaemia 14-19 years (50%), for anaemia of chronic disorder 20-29 and 30-39 years (30% each), iron deficiency anaemia 40-49 years (44.5%) and for anaemia of chronic renal failure 30-39 years (33.3%). Conclusion: Multicentre study with large sample size is warrented to develop more insights about diagnosis and management of severe anaemia. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 631-636